Isolation and partial characterization of a 110-kD dimer actin-binding protein (The Rockefeller University Press, 1986)
Two Triton-insoluble fractions were isolated from Acanthamoeba castellanii. The major non-membrane proteins in both fractions were actin (30-40%), myosin II (4-9%), myosin I (1-5%), and a 55-kD polypeptide (10%). The 55-kD polypeptide did not react with antibodies against tubulins from turkey brain, paramecium, or yeast. All of these proteins were much more concentrated in the Triton-insoluble fractions than in the whole homogenate or soluble supernatant. The 55-kD polypeptide was extracted with 0.3 M NaCl, fractionated by ammonium sulfate, and purified to near homogeneity by DEAE-cellulose and hydroxyapatite chromatography. The purified protein had a molecular mass of 110 kD and appeared to be a homodimer by isoelectric focusing. The 110-kD dimer bound to F-actin with a maximal binding stoichiometry of 0.5 mol/mol of actin (1 mol of 55-kD subunit/mol of actin). Although the 110-kD protein enhanced the sedimentation of F-actin, it did not affect the low shear viscosity of F-actin solutions nor was bundling of F-actin observed by electron microscopy. The 110-kD dimer protein inhibited the actin-activated Mg2+-ATPase activities of Acanthamoeba myosin I and myosin II in a concentration-dependent manner. By indirect immunofluorescence, the 110-kD protein was found to be localized in the peripheral cytoplasm near the plasma membrane which is also enriched in F-actin filaments and myosin I.